Is a rare CXCL8 gene variant a new possible cause or course factor of inflammatory bowel disease? - Gabryel, Marcin; Zakerska-Banaszak, Oliwia; Ladziak, Karolina; Hubert, Katarzyna Anna; Baturo, Alina; Suszynska-Zajczyk, Joanna; Hryhorowicz, Magdalena; Dobrowolska, Agnieszka; Skrzypczak-Zielinska, Marzena (Frontiers in Immunology, 2025)
IntroductionThe pathogenesis of inflammatory bowel diseases (IBD) involves genetic, environmental, immunological, and microbial factors; however, it remains unclear. Pro-inflammatory interleukin 8 (IL-8), encoded by the CXCL8 gene, assumes a crucial chemotactic role in leukocyte migration.MethodsThis study aimed to investigate whether an association exists between IBD and two CXCL8 variants, namely, c.-251A>T (rs4073) and c.91G>T (rs188378669), and IL-8 concentration. We analyzed the distribution of both variants among 353 Polish IBD patients and 200 population subjects using pyrosequencing, competitive allele-specific PCR and Sanger sequencing.ResultsThe c.91T stop-gained allele was significantly more frequent in IBD patients (2.12%) than in controls (0.25%) (p = 0.0121), while the c.-251T allele frequencies were similar (54% vs. 51.5%, p = 0.4955). Serum IL-8 concentrations, measured using ELISA, were higher in IBD patients with the c.91 GG genotype compared to healthy controls (mean, 70.02 vs. 51.5 pg/ml, p<0.01) and patients with c.91 GT (mean, 61.73 pg/ml). Moreover, clinical data indicated that carriers of the c.91T variant need more often corticosteroids and surgical treatment of the disease than GG homozygous IBD patients.ConclusionThis suggest that the CXCL8 c.91T allele may influence IBD manifestation and the course of the disorders in Polish patients, potentially serving as a novel target for future studies and therapeutic approaches.